Changes of force-velocity and power-velocity relationships after training performed on cycle ergometer - Busko, K. (Biology of Sport, 2006)
The aim of this work was the examination of lower limbs muscles force-velocity and power-velocity characteristics changes during the cycle ergometer training. Students of Academy of Physical Education in number of 43 took pari in the research. They were divided in 4 groups and performed various velocity cycle ergometer training. The training encompassed 5 intermittent efforts parted with 2 min pause: group MIO - maximal efforts with the load equal 10% BW, group M5 - maximal efforts with load of 5% BW, group W80 - 3 min efforts with power equal 250 W and pedalling rate of 80 rpm, group W45 - 3 min efforts with power of 250 W and pedalling velocity equal 45 rpm. Control measurements of force-velocity (F-v) and power-velocity (P-v) relationships were taken each Monday before training beginning, during 4 weeks of the experiment and 2 weeks after it. The F-v simple regression equation average direction coefficients gained in all groups during 4 training weeks and after the lst and 2nd week from testing differed significantly according to data gathered before the research. The F-v simple regression equation direction coefficients varied significantly between groups MIO and M5 and between W80 and W45 after the lst week from tests next, between M5 and W80, W45 after the 2nd week of resting period. The highest increase of power Output measured in P-v characteristics was observed in groups M5 and MIO after the lsl week from the experiment by following loads: 2.5%, 5.0% and 7.5% BW and in groups W45 and W80 immediately after 4 week training by loads of 10.0% and 12.5% BW. The lack of crucial differences among groups suggest that the pedalling rates used in trainings had no influence on the after training power Output during F-v and P-v characteristics determination. The training intensity effects the simple force-velocity relationship direction coefficients.